Pengaruh Pemberian Dosis Pupuk NPK dan Jenis Pupuk Hayati terhadap Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium ascalonicum L.) - Hendarto, Kus; Widagdo, Setyo; Ramadiana, Sri; Meliana, Fitria Sita (Universitas Lampung, 2021)
Shallots (Allium ascalonicum L.) is one of the leading vegetable commodities used as food seasoning and traditional medicine. This study aims to see the effect of providing various doses of NPK fertilizer and types of biological fertilizers on the growth and production of shallot plants. This study used a randomized block design (RAK) arranged in a factorial (4 x 2). The first factor is the NPK fertilizer dosage which consists of four levels, namely: N0= 0% (without NPK fertilizer), N1= 50% (25 g/m2), N2= 100% (50 g/m2), and N3= 150% (75 g/m2). The second factor is the type of biological fertilizer which consists of two levels, namely: H1= Grikulan plus fertilizer and H2= EM4. The results showed that the NPK fertilizer dosage treatment up to a dose of 75g/m2 gave the best results on plant growth and development, including the number of leaves, plant height, fresh tuber weight per plant, wind dry tuber weight per plant, and wind dry tuber weight per m2. The growth and development of shallot plants with the application of Grikulan biological fertilizers were better than those of EM4 biological fertilizers. Treatment of NPK fertilizer dosage of 150% or equivalent to 75 g / m2 supplemented with the application of Grikulan plus fertilizer results in higher production, namely the weight of dry tubers per m2 reaching 1674.33 g or equivalent to 11.72 tonnes/ha.Â Keywords : EM4, Grikulan plus, shallots,NPK, yield